Concept of Postal Traffic Quality Control Using the P Card - Miletić, Ruža; Gašpert, Milica; Bošnjak, Ivan (Promet - Traffic&Transportation, 2012)
The concept of operation quality control using the P cardhas proven successful in some other companies, and it had notbeen previously used in the postal traffic. In this concrete study,the statistical data have been gathered on the number of sentand received post according to types and months for the periodbetween Janua~y and December 1998 in domestic and internationaltraffic for Sredi.Ste pasta Zagreb (Zagreb Post OfficesCentre) and in international traffic for Hrvatska pasta (CroatianPost), as well as the number of claim forms and the numberof paid compensations for missing letters ..Based on these, the first step towards operative analysis hasbeen made and the initial knowledge has been acquired. IIshows that the control card can be combined with a number ofotherprocedures that will provide a clear ove1view of the qualityaccording to the given crite1ion (in the concrete case the qualityindicator is the number of claim forms).